Knowledge, attitude and practice about antibiotic use, self-medication and antibiotic resistance among final year medical students and interns at a medical college in Lalitpur, Nepal - Jha, Nisha; Shrestha, Sunil; Shankar, Pathiyil Ravi; Bhandary, Shital (Journal of Chitwan Medical College, 2020)
Background:Antibiotic resistance is a global crisis posing a considerable threat, especially, to developing countries and can cause 10 million deaths by 2050. Medical students as future doctors play an essential role in promoting the rational use of antibiotics. The objectives of this study were to evaluate the respondents’ knowledge, attitude and practice (KAP) regarding antibiotic use, antibiotic self-medication, and antibiotic resistance and compare the KAP among different subgroups of respondents at KIST Medical College, Lalitpur, Nepal. Methods: A cross-sectional study was done among final year medical students and interns from September to October 2019. A structured questionnaire with 22 statements for assessing knowledge, 13 statements for attitude and 12 statements for practice was used as a data collection tool. Differences in the KAP scores among different subgroups were studied using appropriate statistical tests. Results: A total of 131 respondents participated, and 76(58%) were female. Most were from the Brahmin ethnic group 54(41.2%) while 82(62.6%) had relatives in the medical field. Ninety-three (71%) were final year medical students and 38(29%) were medical interns. The knowledge scores were high (76) among most subgroups of respondents. The attitude score was 58 out of 65 and practice score was 6 out of 12. Knowledge scores were higher among female respondents, and practice scores were higher among interns (p=0.002). Conclusions: The study showed good knowledge and attitude regarding antibiotics among the final year medical students and the interns. Interns were found to have a better practice than the final year students for using antibiotics rationally.